A New Species of Trichodesma R. Br. From Burma - Banerjee, S. P. (Indian Forester, 1966)
Trichodesma decurrens Banerjee, sp. nov. (Family: Boraginaceae, Sect. Leioraryum) is described from Burma with illustrations. The unique feature in this species is the decurrent leaves, by which it can be easily differentiated from all other related species in the genus.